The Influence of Social Assistance on Reducing Extreme Poverty in the Social Services of Serdang Bedagai District - Shalsa Febriani; Shinta Nadila; Annisa Fadilah Amir; Mutawaqil Billah Tumanggor; Zamalludin Sembiring (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Social structures always show complex categorization. Wealth and poverty are not only seen as the result of functional interactions in society, but a continuing social dialectic understood. This article explores the social life of beggar communities, focusing primarily on the development of the stigma they face from one side of society, and their efforts to exploit it poverty situation as social capital, as work done regularly to continue life. The research method used here is qualitative with a descriptive ap-proach